ORKLOAD, WORK ENVIRONMENT, MENTAL HEALTH, AND PRIVATE EMPLOYEE PERFORMANCE - Endah Puspitasari; Oka Martini (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Work and work environment on employee performance with mental health as intervening variables. The research method uses a quantitative approach with path analysis based on SEM-PLS. The results showed that workload had a positive and significant effect on employee performance (β = 0.241; p = 0.034) and mental health (β = 0.425; p = 0.000). The work environment also had a positive and significant effect on mental health (β = 0.429; p = 0.000) and employee performance (β = 0.331; p = 0.041). In addition, mental health has been shown to have a significant positive effect on employee performance (β = 0.366; p = 0.001). Further analysis revealed that mental health mediated the relationship between workload and performance (β = 0.155; p = 0.007) as well as between the work environment and employee performance (β = 0.157; p = 0.037). These findings confirm that employee performance is not only determined by the physical aspects of work and work environment conditions, but also influenced by mental health stability. As such, companies need to manage workloads proportionately, create a conducive work environment, and provide support for employees' mental health to improve performance and reduce turnover